Effects of oil price on Turkish stock market - Akbarli, Ehtiram (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: The price of oil is one of the most important macroeconomic factors that can influence the countries' economies. Because oil is the main source of energy for most countries, any fluctuation in the price of oil can affect companies' profits and hence their stock price. This study investigates oil price’s effect on the Turkish Stock Market. After determining that there is cointegration among the variables, Vector Error Correction Model is used to study this relationship. The results suggest that in the long run, increasing oil price has a significantly positive impact on the Turkish Stock Market. The Granger Causality test is also run to check possible short-run impact of oil price on the Turkish Stock Market, but the Granger Causality results suggest that oil price does not have a significant effect on the Turkish Stock Market in the short-run.

ÖZET: Petrol fiyatları ülkelerin ekonomilerini etkileyen en önemli makroekonomik faktörlerden biridir. Petrolün temel enerji kaynağı olması sebebiyle, petrol fiyatlarındaki dalgalanmalar şirketlerin karlılıklarını ve dolayısıyla hisse senedi fiyatlarını da etkileyebilmektedir. Bu çalışmada petrol fiyatlarının Türkiye Borsası üzerindeki etkisi incelenecektir. Çalışmada kullanılan değişkenler arasında eşbütünleşmenin var olduğunun belirlenmesi üzerine, çalışmada Hata Düzeltme Modeli uygulanmıştır. Model sonuçlarına göre petrol fiyatlarının Türkiye Borsası üzerinde anlamlı ve pozitif etkisi vardır. Çalışmada ayrıca kısa dönem ilişkiyi test etmek adına Granger Nedensellik testi de uygulanmıştır. Bu test sonuçlarında ise petrol fiyatlarının Türkiye Borsası üzerindeki etkisinin kısa dönemde anlamlı olmadığı sonucuna ulaşılmıştır.
Petrol fiyatının Türkiye hisse senedi pazarına etkisi
Keywords: Crude Oil Price; Stock Price; Cointegration; Vector Error Correction; Model Granger Causality; Ham Petrol Fiyatı; Hisse Senedi Fiyatı; Eşbütünleşme; Hata Düzeltme Modeli; Granger Nedensellik